Lipids are required for the development of Brazil nut allergy: the role of mouse and human iNKT cells. Issue 1 (9th November 2012) - Mirotti, L.; Florsheim, E.; Rundqvist, L.; Larsson, G.; Spinozzi, F.; Leite‐de‐Moraes, M.; Russo, M.; Alcocer, M.
Abstract Background Lipids are required for mice sensitization to Ber e 1, Brazil nut major allergen. Here, we characterized different lipid fractions extracted from Brazil nuts and the lipid‐binding ability of Ber e 1. Further, we determined their in vivo ability to induce Ber‐specific anaphylactic antibodies and the role of invariant natural killer T (iNKT) cells in this process. Methods Wild‐type (WT) and iNKT cell‐deficient mice were sensitized with Ber e 1 and specific lipid fractions, and anaphylactic antibodies were measured by enzyme‐linked immunosorbent assay (ELISA) and passive cutaneous anaphylaxis (PCA). The lipid‐binding characteristic of Ber e 1 (Ber) was established by using fluorescent probes and 15N‐labeled NMR. In vitro production of IL‐4 was determined in Ber/lipid C‐stimulated mouse iNKT cells and human T‐cell lines containing NKTs primed with CD1d+C1R transfectants by flow cytometry and ELISA, respectively. Results Only one specific lipid fraction (lipid C), containing neutral and common phospholipids, induced Ber anaphylactic antibodies in mice. Ber e 1 has a lipid‐binding site, and our results indicated an interaction between Ber e 1 and lipid C. iNKT‐deficient mice produced lower levels of anaphylactic antibodies than WT mice. In vitro, Ber/lipid C‐stimulated murine iNKT cells produced IL‐4 but not IFN‐gamma. Human T‐cell lines derived from nut‐allergic patients produced IL‐4 to Ber/lipid C in a CD1d− and dose‐dependent manner. Conclusion Lipid fraction C from Brazil nut presents an essential adjuvant activity to Ber e 1 sensitization, and iNKT cells play a critical role in the development of Brazil nut‐allergic response.